The Influence of Professionalism and Organizational Commitment on The Performance of Nurses at The Kertosono Regional Hospital - Shintia Novotna Katoda; Nurmiati Muchlis; Yuliati Yuliati (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Because nurse performance has a major impact on the healthcare industry and the standard of hospital services, it is a strategic issue. Maintaining and enhancing nurses' work performance is essential. The purpose of this study is to determine the variables that either directly or indirectly influence nurse performance at Kertosono Regional Hospital, including professionalism, organizational commitment, and job satisfaction. Using Likert scale questionnaires and secondary data gathered from nurse performance assessments, the study used cross-sectional methodologies. This research was conducted at Kertosono Regional Hospital start from May to July 2023. Sample sizes were determined using the Slovin formula, resulting in 140 samples out of 195 total populations. Data were analyzed with smartPLS 3.3, conducting hypothesis testing in two stages: outer model testing for indicator validity and reliability, and inner model testing to confirm hypotheses. The results showed that: professionalism (path coefficient = 0.356, p = 0.000), organizational commitment (path coefficient = 0.330, p = 0.001), and job satisfaction (path coefficient = 0.304, p = 0.002) directly positively impact nurse performance. Additionally, professionalism (path coefficient = 0.261, p = 0.040) and organizational commitment (path coefficient = 0.218, p = 0.047) directly influence nurse performance, mediated by job satisfaction. Indirect effects were observed for professionalism (path coefficient = 0.108, p = 0.015) and organizational commitment (path coefficient = 0.100, p = 0.033) on the effectiveness of nurses through job satisfaction. The study's findings demonstrate that organizational commitment and professionalism have a favorable, considerable impact on nurses' job satisfaction and performance at Kertosono Regional Hospital. Furthermore, job satisfaction has a direct impact on nurses' performance, whereas job satisfaction indirectly influences professionalism and organizational commitment in nurses. Keywords: Job Satisfaction, Nurse Performance, Organizational Commitment, Professionalism